Epigenetic silencing of transposable elements: A trade-off between reduced transposition and deleterious effects on neighboring gene expression - Hollister, Jesse D.; Gaut, Brandon S. (Genome Research, 2009)
Transposable elements (TEs) are ubiquitous genomic parasites. The deleterious consequences of the presence and activity of TEs have fueled debate about the evolutionary forces countering their expansion. Purifying selection is thought to purge TE insertions from the genome, and TE sequences are targeted by hosts for epigenetic silencing. However, the interplay between epigenetic and evolutionary forces countering TE expansion remains unexplored. Here we analyze genomic, epigenetic, and population genetic data from Arabidopsis thaliana to yield three observations. First, gene expression is negatively correlated with the density of methylated TEs. Second, the signature of purifying selection is detectable for methylated TEs near genes but not for unmethylated TEs or for TEs far from genes. Third, TE insertions are distributed by age and methylation status, such that older, methylated TEs are farther from genes. Based on these observations, we present a model in which host silencing of TEs near genes has deleterious effects on neighboring gene expression, resulting in the preferential loss of methylated TEs from gene-rich chromosomal regions. This mechanism implies an evolutionary tradeoff in which the benefit of TE silencing imposes a fitness cost via deleterious effects on the expression of nearby genes.
10.1101/gr.091678.109